Smart Medkit. Issue 1 (January 2021) - Lenin, S.B.; Pushparaj, S.; Adithya, M.; Murugesan, S.; Balaji, N.; Gurupriyan, J.
Abstract: The medical field plays a vital role in our day-to-day life. In recent years, it achieved a tremendous growth in advancements and technologies. Along with the maladies, the diagnosing and curing techniques are also evolved. Despite these advancements, the death rate due to medical errors has not yet decreased. To reduce these medical errors, we have designed a system which reduces some of the common medical errors such as improper medication timing, under and over dosage of medicines and delay in treatment. This system reminds the patient about their pills using voice message using playback module and speaker and it also dispenses the pills via slot arrangement controlled by stepper motor. If the patient ignores the voice message an SMS alert is sent to the patient's attender and the caretaker. It also has an emergency subsystem which can be used in case of any emergency situation to the patient and it also allows the caretaker to send the prescribed medicines list to the caretaker via SMS.